Galangin 3-benzyl-5-methylether derivatives function as an adiponectin synthesis-promoting peroxisome proliferator-activated receptor γ partial agonist. (15th January 2022) - Ko, Hyejin; Jang, Hongjun; An, Seungchan; Park, In Guk; Ahn, Sungjin; Gong, Junpyo; Hwang, Seok Young; Oh, Soyeon; Kwak, Soo Yeon; Choi, Won Jun; Kim, Hyoungsu; Noh, Minsoo
Graphical abstract: Abstract: The upregulation of adiponectin production has been suggested as a novel strategy for the treatment of metabolic diseases. Galangin, a natural flavonoid, exhibited adiponectin synthesis-promoting activity during adipogenesis in human bone marrow mesenchymal stem cells. In target identification, galangin bound both peroxisome proliferator-activated receptor (PPAR) γ and estrogen receptor (ER) β. Novel galangin derivatives were synthesized to improve adiponectin synthesis-promoting compounds by increasing the PPARγ activity of galangin and reducing its ERβ activity, because PPARγ functions can be inhibited by ERβ. Three galangin 3-benzyl-5-methylether derivatives significantly promoted adiponectin production by 2.88-, 4.47-, and 2.76-fold, respectively, compared to the effect of galangin. The most potent compound, galangin 3-benzyl-5, 7-dimethylether, selectively bound to PPARγ ( Ki, 1.7 μM), whereas it did not bind to ERβ. Galangin 3-benzyl-5, 7-dimethylether was identified as a PPARγ partial agonist in docking and pharmacological competition studies, suggesting that it may have diverse therapeutic potential in a variety of metabolic diseases.